(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Background: Persistent infection with high-risk Human Papilloma Virus (HPV) causes development of cervical cancer. Among the high risk group, HPV-16 accounts for 50% & HPV-18 accounts for 12% of cervical cancer. Objective: The current sudy aimed to evaluate the prevalence of HPV genotype 16 and 18 in high grade cervical intraepithelial neoplasia (CINII&III) and cervical cancer. Methods: This descriptive type of cross-sectional observational study was carried out in colposcopy clinic of Mymensingh Medical College Hospital (MMCH), Bangladesh, from July 2012 to June 2013. Women with colposcopically diagnosed high-grade CIN and clinically diagnosed cervical carcinoma were enrolled. Pregnant & menstruating women were excluded from this study. Colposcopy guided cervical biopsy were taken from high grade CIN with loop electrosugical excision procedure (LEEP) and wedge biopsy were taken from cervical cancer. All the specimen were reviewed by histopathologist to confirm the diagnosis. Extra sample of specimen were sent to the Department of Microbiology and Hygiene of Bangladesh Agriculture University, Mymensingh for the detection of HPV-16 & 18 DNA by Polymerase Chain Reaction (PCR). Result: Out of 71 samples, histopathologically 4.2% was diagnosed as chronic cervicitis, 8.5% CIN I, 26.8% CIN II, 16.9% CIN III, 40.8% squamous cell carcinoma and 2.8% adenocarcinoma of cervix. The results revealed that 30 cases were positive for HPV-16, 06 cases for HPV-18 and 04 cases for both. In this study, the prevalence of HPV- 16 & 18 infection was 56.3%. Infection found to be higher in women aged between 45 and 54 (P<0.01). Most of them were from low socioeconomic status (P<0.01) and married at an early age ranging from 11 to 15 (P<0.01). It was found that multiparity correlated higher rate of HPV positivity than only one or two pregnancy, but statistically it was not significant (P>0.05). Conclusion: The high prevalence of HPV-16 and 18 in high grade CIN and cervical cancer samples suggests that vaccination against HPV-16 and 18 may be effective in bringing down the cervical cancer incidence in Bangladesh. J Bangladesh Coll Phys Surg 2018; 36(3): 112-117